Examining Feminist Perspective In Abolishing Sex Trafficking Case Study: Sex Trafficking In Thailand - Naeli Fitria (Journal Research of Social Science, Economics, and Management, 2022)
Debate between feminist perspectives has become contested both in academic sphere and policy implementation in addressing sex trafficking. Human rights aspects remain critical either to liberate or to abolish sex trafficking. Radical feminist perspective defends the argument to eliminate sex trafficking due to the existence of physical abuses and sexual harassment within the sex industry and the cycle of sex trafficking. Contrastingly, liberal feminist also making efforts in liberating the rights of women to seek a job to be sex workers due to women’s autonomy and rational choice as well as the influence of global capitalist system. Such debates, furthermore, cannot be distinguished from the influence of the rooted theories, for instance, postcolonial feminism which argue that sex trafficking is inevitable notably for the colonised countries since the women are triggered to seek for decent income through migrating to another country. In addition, poststructuralist feminism highlighted the crucial point of women’s autonomy and rights. This study argues that the attempts to abolish sex trafficking and prostitution remain relevant to date since women who work as sex workers should be acknowledged as the victims of sex trafficking. Taking sex trafficking and prostitution in Thailand as the case study has eventually found that social norms and corrupted officials have become major barriers in combating sex trafficking and prostitution until recently. The government strategies together with the regional efforts hereby the Association of Southeast Asia Nations (ASEAN) in combating the crime of sex trafficking have shown that challenges ahead remain exist.